Kajian Konsep Dasar Supervisi Pendidikan - Ma'ruf, Insanul; Jamilus (Jurnal Tinta, 2025)
Educational supervision is a crucial aspect in efforts to improve the quality of learning and teacher professionalism in educational institutions. In practice, supervision is often misunderstood merely as an administrative oversight activity, whereas in essence, it serves a broader function as a process of continuous teacher development and guidance. This study aims to explore the fundamental concepts of educational supervision through a literature review approach. The study focuses on six key areas: the terminology of supervision, the objectives of supervision, the principles of supervision, types of supervision, functions of supervision, and the dimensions of educational supervision. The findings indicate that supervision, when implemented in a planned, participatory, and teacher-centered manner, can significantly enhance the quality of teaching and learning. Effective supervision must be grounded in democratic, objective, and educative principles, while also taking into account technical, administrative, personal, and social dimensions. By understanding these fundamental concepts, supervisors can carry out their roles more professionally, humanely, and with a direct impact on teacher performance and overall educational quality.